Evaluation of Clinical Competence and Job Satisfaction and Their Related Factors Among Emergency Nurses in Palestinian Hospitals - Basma Salameh PhD, RN; Diya Basem Suleiman Amarneh MSc, RN; Jihad Abdallah PhD; Ahmad Ayed PhD, RN; Bahaaeddin M. Hammad PhD, RN (SAGE Publishing, 2023)
Introduction Nurses are responsible for providing primary care to millions of patients, and emergency nurses serve on the frontline in providing care for mildly to severely critically ill patients. Objectives This study aims to assess and evaluate the clinical competence and its related factors among emergency nurses in Palestinian hospitals. Methods A cross-sectional study was conducted among 170 nurses working in the emergency units of hospitals in the West Bank, Palestine. Data collection utilized the Nurse Competence Scale, and the Job Satisfaction Scale. Results The results showed that only 33(19.4%) of the participants exhibited a good level of clinical competence, with none reaching the very good level. Among them, the highest proportion of good level 60 (35.3%) was in the helping role, while the lowest 38 (22.4%) was in ensuring quality. About 35% of nurses reported very low or low job satisfaction, while 58% had high or very high job satisfaction. Additionally, the results revealed a statistically significant relationship between clinical competence and job satisfaction ( P  < 0.05). Both clinical competence and job satisfaction were positively correlated with age and experience. Conclusion The study found a significant relationship between demographic characteristics (e.g., education, experience, and marital status) and clinical competency among emergency nurses. Notably, less than half of the participants demonstrated good clinical competency, with none reaching a very good level. The highest scores were observed in the helping role domain, while the lowest were in the ensuring quality domain. Furthermore, clinical competence was found to be significantly associated with job satisfaction. Consequently, enhancing nurses' clinical competency will lead to an improvement in the quality of patient care.